EDUCATIONAL SERVICES MARKETING STRATEGY IN MADRASAH - Zamroni, Zamroni; Jannah, Imanisa Roudlotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research stems from the researcher's interest in the marketing strategy for educational services carried out by Madrasah Ibtidaiyah Ma'arif NU 003 Samarinda; because of the intense competition in marketing in educational services and MI Ma'arif NU 003 Samarinda was able to survive and compete superior to other education providers. This study aimed to determine the Education Services Marketing Strategy at MI Ma'arif NU 003 Samarinda and add insight and knowledge about the Education Services Marketing Strategy at MI Ma'arif NU 003 Samarinda. This type of research is qualitative research, and the targets of this research are all school members involved in marketing educational services. The method used is the method of content analysis (content analysis). This research's data source is observation and educational service strategy documents for MI Ma'arif NU 003 Samarinda. To complete the research data, the researcher interviewed the head of the Madrasah, the head of PPDB and the deputy for student affairs. Technical data analysis is carried out by collecting, condensing, presenting, and concluding. In this case, the researcher reveals the factors of consumer behaviour and marketing strategies implemented at MI Ma'arif NU 003 Samarinda. The results of this study indicate that the marketing strategy for educational services has fulfilled two strategies, namely the competitive strategy (mind share strategy) and the marketing mix (marketing mix).